Asymptotic Expansions of the Wavelet Transform for Large and Small Values of b. (27th September 2009) - Pathak, R. S.; Pathak, Ashish
Abstract : Asymptotic expansions of the wavelet transform for large and small values of the translation parameterb are obtained using asymptotic expansions of the Fourier transforms of the function and the wavelet. Asymptotic expansions of Mexican hat wavelet transform, Morlet wavelet transform, and Haar wavelet transform are obtained as special cases. Asymptotic expansion of the wavelet transform has also been obtained for small values ofb when asymptotic expansions of the function and the wavelet near origin are given.